2010
DOI: 10.1016/j.jbankfin.2009.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Market conditions, default risk and credit spreads

Abstract: This study empirically examines the impact of the interaction between market and default risk on corporate credit spreads. Using credit default swap (CDS) spreads, we find that average credit spreads decrease in GDP growth rate, but increase in GDP growth volatility and jump risk in the equity market. At the market level, investor sentiment is the most important determinant of credit spreads. At the firm level, credit spreads generally rise with cash flow volatility and beta, with the effect of cash flow beta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
131
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 275 publications
(159 citation statements)
references
References 46 publications
(35 reference statements)
10
131
0
Order By: Relevance
“…Nayak (2010) finds that corporate bond spreads are affected by investor sentiment. Tang and Yan (2010) show that market-wide credit spreads negatively depend on investor sentiment. We add to this literature by showing that low investor sentiment leads to high risk factor correlation and, ultimately, high bond correlation.…”
mentioning
confidence: 97%
“…Nayak (2010) finds that corporate bond spreads are affected by investor sentiment. Tang and Yan (2010) show that market-wide credit spreads negatively depend on investor sentiment. We add to this literature by showing that low investor sentiment leads to high risk factor correlation and, ultimately, high bond correlation.…”
mentioning
confidence: 97%
“…The credit rating information is another important factor in determining CDS spreads (Cossin and Hricko, 2001). Tang and Yan (2008), however, use Moody's KMV Expected Default Frequency (EDF), instead of Moody's and S&P credit ratings, as a measure of default probability. They claim that EDF has the advantage of being frequently updated of credit conditions as the indicator is based on the stock price of the reference firm.…”
Section: Determinants Of Cds Spreads: Theoretical and Empirical Evidencementioning
confidence: 99%
“…This result holds for all rating categories and the riskless curve Altman et al (2005) Firm-specific variables add little in terms of explanatory power or incremental statistical significance to the CDS spread Tang and Yan (2006) The paper constructs liquidity proxies to capture various aspects of CDS liquidity and examines its impact with adverse selection and inventory constraints. They find that both liquidity level and liquidity risk are significant factors in determining CDS spreads Cremers et al (2008) Option-implied jump risk measures explain a significant part of observed credit spread as measured by CDS spread Tang and Yan (2008) Macroeconomic conditions have a significant impact on CDS spreads. Also, it provides further evidence on the importance of the interaction between market conditions and firm-specific characteristics Imbierowicz (2009) The paper suggests that portfolio positions have to be evaluated constantly and related to their truly fundamental value, otherwise you risk mispricing, and that present structural pricing models do not capture all important factors on CDS and that we must consider the importance of forward-looking macro-indicators as well as liquidity measures and the incorporation of implied volatilities Li (2007) Systematic risk proportion has a negative and significant effect on the CDS spreads after including variables that are suggested by theories of default risk and the extant empirical evidence.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations